DNA methylation in PRDM8 is indicative for dyskeratosis congenita - Weidner, Carola I.; Lin, Qiong; Birkhofer, Carina; Gerstenmaier, Uwe; Kaifie, Andrea; Kirschner, Martin; Bruns, Heiko; Balabanov, Stefan; Trummer, Arne; Stockklausner, Clemens; Hoechsmann, Britta; Schrezenmeier, Hubert; et al. (Oncotarget, 2016)
Dyskeratosis congenita (DKC) is associated with impaired telomere maintenance and with clinical features of premature aging. In this study, we analysed global DNA methylation (DNAm) profiles of DKC patients. Age-associated DNAm changes were not generally accelerated in DKC, but there were significant differences to DNAm patterns of healthy controls, particularly in CpG sites related to an internal promoter region of PR domain containing 8 (PRDM8). Notably, the same genomic region was also hypermethylated in aplastic anemia (AA) - another bone marrow failure syndrome. Site-specific analysis of DNAm level in PRDM8 with pyrosequencing and MassARRAY validated aberrant hypermethylation in 11 DKC patients and 27 AA patients. Telomere length, measured by flow-FISH, did not directly correlate with DNAm in PRDM8. Therefore the two methods may be complementary to also identify patients with still normal telomere length. In conclusion, blood of DKC patients reveals aberrant DNAm patterns, albeit age-associated DNAm patterns are not generally accelerated. Aberrant hypermethylation is particularly observed in PRDM8 and this may support identification and classification of bone marrow failure syndrome
EVALuna2:25740